On farm grain storage – potential opportunity or risk- meeting the demands of food safety and quality, an Australian perspective - Botta, Peter; Ballati, Judy (Julius-Kühn-Archiv, 2018)
Traceability, product identity, food safety and quality assurance are increasingly required by end users and customers. The Australian on farm storage system has a unique opportunity to deliver grain to meet these requirements, provided the system is set up and managed to ensure the end product meets the market requirement. Australian grain growers are becoming more aware of the changing nature of markets and their requirements, and the importance of managing storage to meet food safety requirements. With the increasing change in storage dynamics in Australia from a central receival system to a range of storage entities, of which on farm storage is becoming a major player, there is a growing need for the grains industry to ensure all who can affect grain quality and food safety are aware of and can meet their obligations. There are many challenges for Australian growers to manage; including managing existing facilities, investing in new facilities, managing insects, managing grain quality and ensuring treatments are used in accordance with best practice. Despite these challenges, there are many opportunities and potential for the on-farm storage system to meet the demands required of them to deliver a quality and food safe product to the end-user. This paper discusses the on-farm grain storage system, management of and the opportunity and risks for growers and end users to work together to ensure a quality and food safe product is delivered to the end-user. Traceability, product identity, food safety and quality assurance are increasingly required by end users and customers. The on farm storage system has a unique opportunity to deliver grain to meet these requirements, provided the system is set up and managed to do this in collaboration with the end user and market. Whilst grain growers are aware of the changing nature of markets and their requirements, it is fair to say food safety and how they might affect this is relatively new in their thinking. With the increasing change in storage dynamics from a central receival system to a range of storage entities, of which on farm storage is becoming a major player, there is a growing need for the grains industry to ensure all who can affect grain quality and food safety are aware of and can meet their obligations. There are many challenges for growers to manage; including managing existing facilities, investing in new facilities, managing insects, managing grain quality and ensuring treatments are used in accordance with best practice. Despite these challenges, there are many opportunities and potential for the on-farm storage system to meet the demands required of them to deliver a quality and food safe product to the enduser and customer. This paper discusses the on-farm grain storage system, management of the system and the opportunity and risks for growers and end users to work together to ensure a quality and food safe product is delivered to the enduser and customer.